Catalytic oxidation of NO over LaMnO3(001) surface: A DFT-based study. (8th October 2021) - Xiang, Chao; Peng, Cheng; Xu, Xiangjun; Zhou, Tianguo
Abstract: NO oxidation over LaMnO3 (001) surface was studied using first-principle calculations based on density functional theory (DFT). The calculated results indicate that the surface energies of (001) are lower than that of the (011) and (111) surfaces. Three adsorbates (O2 NO and NO2 ) after adsorption are activated due to remarkable elongation of bond length, notable change in DOS and large electron transfer. The analysis of the electron localization function (ELF) reveal the typical feature of a ionic bond in the Mn-N and Mn-O bond intersecting planes. Difference charge density (DCD) analysis show that electron accumulation occurs at the Mn-O and Mn-N bonds as charge is transferred from adsorbate (NO, O2 or NO2 ) to the substrate, so that the ability bonding of the adsorbate and substrate is enhanced. The reaction of NO adsorbed at Mn2 with Oc is faster and more feasible due to the low energy barrier and short Oc -N bond distance. Dissociation of O2 is an exothermic process (−1.290 eV) with a small activation energy (0.345 eV). The NO activation and desorption of NO2 are energetically the most demanding steps.